Sustainable Solar Powered Multi Nozzle Pesticide Sprayer for Improved Production - Rai, Rahool; Khursheed, Rehan; Rehman, Sadiq Ur; Jamil, Rabiya (IJPTE, 2024)
In agriculture, automation of spraying has boosted farm productivity. As a result, the labor issue has been resolved. However, the situation is different in a nation like Pakistan. Automation in the agricultural sector is challenging in these arid regions because the most Pakistani farmers are struggling financially. Therefore, the wide use of the manually operated sprayer is still common in majority of the areas of Pakistan. Due to its affordability, design, and versatility, manually lever driven backpack sprayers are much sought after by small-scale farmers. Two types of sprays are utilized in Pakistani farms: fuel-operated pumps and hand-operated ones. The primary disadvantage of a hand-operated spray pump is that its user cannot use it continuously for longer than five to six hours. Due to fatigue, long working hours are impossible without integration of any other energy, but a gasoline-operated spray pump needs fuel, which is costly and difficult to find in remote areas. Therefore, the work represents the integration of renewable energy (solar power) and a manually operated mechanism to achieve sustainability with increased efficiency and reduced human efforts. It is observed from the results that around 2.5 times increased discharge was achieved, and time is reduced by 2.5 times. The proposed idea drives a solar powered multi-nozzle with pump, which sprays pesticide uniformly, along with environmental benefits. In result, pesticide sprayer reduces farmer fatigue and sprays at its highest pace in the shortest amount of time without requiring fuel.